FASHION AS A FETISH TO CONSUMPTION IN CAPITALIST SOCIETY (REMUNOM, 2025)
The main objective of this study is to discuss fashion as a commodity, with an emphasis on the fetish of consumerism in capitalist society. One way to understand the complexity of capitalist society is to have a multidisciplinary view of how things change over time. It is no different with fashion, which emerged and promoted a new form of commodity production, requiring qualified and diversified labor. Methodologically, it is plausible to highlight that this study is basic in nature and descriptive in objective. As for the procedural method, a bibliographical method with a qualitative approach was adopted. As for the information collection techniques, a literature review of secondary sources was used. The results indicate that the impacts caused by the transformative demands of the flow and counterflow of fashion standards follow the same logic of the capitalist market, resulting in environmental damage and causing several social problems. In conclusion, it can be inferred that the demand for fashion production to meet market standards has caused precariousness in the lives of families and even the destruction of entire ecosystems.